1986
DOI: 10.1128/jb.166.2.412-416.1986
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the chromosomal locations of four Bacillus subtilis genes which code for a family of small, acid-soluble spore proteins

Abstract: The chromosomal locations of four genes which code for small, acid-soluble spore proteins (SASP) in Bacillus subtilis have been determined. Although these four genes code for extremely homologous small, acid-soluble spore proteins (>65% sequence identity), the genes are not clustered but are megaterium there are at least seven genes coding for SASPs with greater than 65% amino acid sequience identity and that all of these genes are expressed (4). This identification of an extended, divergent multigene family… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
20
0

Year Published

1988
1988
1996
1996

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 13 publications
2
20
0
Order By: Relevance
“…Similar analyses of drug-resistant clones derived from transformation with pJH101 derivatives carrying the SASP-C, SASP-C-3, SASP-C-4, or gpr gene indicated that these plasmids had also integrated into the chromosome by a Campbell-type mechanism at the site of the cloned gene carried on the transforming plasmid (data not shown). This was also found previously, when pJH101 derivatives were integrated into the B. subtilis chromosome (2,5,12).…”
supporting
confidence: 61%
See 2 more Smart Citations
“…Similar analyses of drug-resistant clones derived from transformation with pJH101 derivatives carrying the SASP-C, SASP-C-3, SASP-C-4, or gpr gene indicated that these plasmids had also integrated into the chromosome by a Campbell-type mechanism at the site of the cloned gene carried on the transforming plasmid (data not shown). This was also found previously, when pJH101 derivatives were integrated into the B. subtilis chromosome (2,5,12).…”
supporting
confidence: 61%
“…While there is only a single type B SASP gene, there are at least seven genes which code for type A/C SASP of extremely similar amino acid sequence, with two of these genes coding for the two major SASP of this type, termed SASP-A and SASP-C in B. megaterium (6)(7)(8)11). The multigene nature of the SASP-A/C gene family as well as a single SASP-B gene have also been found in B. subtilis, and to date five SASP genes have been cloned and mapped in this organism (2,3,12). Strikingly, all five genes, including four SASP-A/C-type genes, are scattered about the chromosome (12).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Site-specific integration of foreign DNA linked to chromosomal sequences by homologous recombination has been described for many microorganisms and used to generate insertion mutants (32,33), to map and clone genes (6,18,30), to introduce defined deletions (17, 34), and to stabilize and amplify important traits (25,38).…”
mentioning
confidence: 99%
“…Induction of this phospho-13-glycohydrolase activity coincided with the appearance of a new 55-kDa protein cross-reacting with anti-LacG antibodies that had a size similar to that of LacG but a higher isoelectric point (pI 5.2) and was not found in wild-type cells during growth on lactose. Since the phospho-13-glycohydrolase activity and this protein with a pI of 5.2 were highly induced in both mutant and wild-type cells during growth on cellobiose that is likely to be transported via a phosphoenolpyruvate-dependent phosphotransferase system, we propose that this induced activity is a phospho-13-glucosidase that also hydrolyzes lactose-6-phosphate.Site-specific integration of foreign DNA linked to chromosomal sequences by homologous recombination has been described for many microorganisms and used to generate insertion mutants (32,33), to map and clone genes (6,18,30), to introduce defined deletions (17, 34), and to stabilize and amplify important traits (25,38).Recently, integration systems have been developed for Lactococcus lactis, a gram-positive bacterium widely used in industrial food fermentations, whereby randomly cloned chromosomal DNA (26), prophage sequences (5), natural plasmid DNA (13, 36), transposon DNA (4, 19) and insertion elements (37, 40) were used to provide the required homology. In some cases, multicopy integration of sequences to a level of about 15 copies per chromosome has been obtained, but their stability was low in the absence of selective pressure (5,26).…”
mentioning
confidence: 99%